Integrity framework for public investment. - (:unkn) unknown (My University, 2016)
Öffentliche Investitionen, darunter vor allem solche in Infrastruktur, sind entscheidend für nachhaltiges Wirtschaftswachstum sowie für öffentliche Dienstleistungen. Allerdings sind sie auch anfällig für Korruption. Die Publikation analysiert die direkten und indirekten positiven Effekte öffentlicher Investitionen. Außerdem beschreibt sie die Korruptionsrisiken in jeder Phase des Investitionsprozesses, stellt Instrumente vor, um Integrität zu fördern, und schildert Beispiele, wie diese erfolgreich im öffentlichen und privaten Sektor eingesetzt wurden.

Public investment, and particularly infrastructure investment, is important for sustainable economic growth and development as well as public service provision. However, it is also vulnerable to capture and corruption. This publication examines the direct and indirect benefits of public investment if carried out in a clean and efficient manner. It provides a Framework for Integrity in Public Investment, mapping out risks of corruption at each phase of the investment cycle. It also identifies tools and mechanisms to promote integrity in the public investment cycle and provides examples of their successful implementation in both the public and private sectors.
Keywords: Öffentliche Investition; Infrastrukturinvestition; Verwaltungshandeln; Korruption; Transparenz; Wirtschaftskriminalität; Compliance; Internationaler Vergleich